Determinants of intention to adopt online crowdfunding services among SMEs in Northwestern Nigeria - Kazaure, Mansur Ahmed (2021)
Access to financing is one of the major constraints to the growth and development of Small and Medium Enterprises (SMEs) in Nigeria. The main sources of SMEs financing besides personal savings are commercial and development banks, and to some extent, government approved intervention schemes for SMEs funding. Unfortunately, bank-lending conditions in terms of collateral and interest rates have not encouraged the sector to obtain the desired credits from commercial and development banks. Several government intervention programs were initiated in the past but the problem of accessing fund by SMEs remained unsolved. Consequently, SMEs in developed and emerging economies have resorted to an innovative financing known as online crowdfunding. However, the usage of this alternative is very low in developing countries such as Nigeria. Therefore, the main aim of the current study is to explore the determinants of SMEs intention towards the adoption of online crowdfunding in Northwestern Nigeria. The determinants of the online crowdfunding adoption intention used in this study are derived from the Theory of Planned Behavior and the Technological Acceptance Model with additional two variables adopted from the AIDA Model. This research employed Survey Research Design and the population for the study comprised 12,523 SMEs owners in the three states (Kano, Kaduna and Katsina) of Northwestern Nigeria. Data was collected from a sample of 407 SMEs’ owners through a survey questionnaire. Descriptive Statistics and Structural Equation Modeling using Smart-PLS 3.0 graphics were deployed in analyzing the data. Results show that perceived usefulness, perceived ease of use, use of social media, awareness and attitude have significant positive effects on SMEs intention to adopt online crowdfunding in the area of study. Moreover, the finding reveal that subjective norms and perceived behavioral control have insignificant effect on SMEs intention to adopt online crowdfunding in Northwestern Nigeria. Furthermore, the moderation test revealed the positive effect of trust on perceived ease of use, the use of social media and subjective norms on online crowdfunding intention among SMEs owners in Northwestern Nigeria. Contrarily, trust failed to moderate the effects of perceived usefulness, awareness, attitude, subjective norms and perceived behavioral control on online crowdfunding intention among SMEs owners. Further, among the three SMEs Sectors, the manufacturing sector has the highest intention, followed by the services sector and the agricultural sector. Therefore, based on the findings of the study, which indicate that SMEs owner have a high level of crowdfunding intention, it is recommended that government and policymakers should develop a policy framework that will motivate them to actualize their intention of adopting online crowdfunding to finance their businesses. Theoretically, the study is among the first few studies to the integrate Theory of Planned Behavior and Technological Acceptance Model to measure business owners’ intention of adopting online crowdfunding. Thus, it is also recommended that future research should test the model proposed in this study in other Nigerian geo-political zones as well as other developing countries for the comparison of finding to establish this replication or otherwise.